Relationship Between Serum Albumin Levels And Pulmonary Edema In Glomerulonephritis Patients - Fikria, Nabilla; Partingrum, Dwi Lestari; Kuntjoro, Lydia Purna Widyastuti Setjadiningrat; Meutia , Yurida Binta (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: Glomerulonephritis is an inflammatory disease of the glomerulus that causes changes in permeability, changes in kidney’s structure, and function of the glomerulus. Hypoalbuminemia in glomerulonephritis can decrease oncotic pressure resulting in extravasation of fluid into the interstitium. In severe hypoalbuminemia, extravasation of fluid can result in pulmonary edema. The subjective of this study was to analyze the correlation between serum albumin and the incidence of pulmonary edema by chest x-ray in patients with glomerulonephritis. Methods: The samples of this study were collected by purposive sampling using secondary data from the medical records of Dr. Kariadi Hospital in Semarang with a total of 46 subjects from January 2016-January 2021. The serum albumin was categorized as normal if serum albumin was >3,5 g/dL, mild hypoalbuminemia if serum albumin was 2.5-3.5 g/dL and severe hypoalbuminemia if serum albumin was <2.5 g/dL. Result: Mann Whitney test showed a significant relationship between between serum albumin and the incidence of pulmonary edema by chest x-ray in patients with glomerulonephritis (p = 0.016). A higher mean rank was found in patients with pulmonary edema compared to patients without pulmonary edema. Conclusion:There is a significant relationship between serum albumin and the incidence of pulmonary edema by chest x-ray in patients with glomerulonephritis. Patients with lower serum albumin have a greater tendency to develop pulmonary edema than patients with higher serum albumin.